Perceptions and Attitudes of Elementary School Class Teachers as Facilitators of Inclusive Education for Children with Special Needs - Ranti Novianti; Asep Fatoni Rizal; Fadly Halim Hutasuhut; Salma Nadiyah; Yoga Budhi Santoso; Atma Widia (INCLUSIVE EDUCATION, 2022)
The problem that is currently happening at SD Negeri Babakan 01 in South Tangerang City is that regular teachers at the school in educational services do not involve children with special needs directly so children with special needs who are in the class are not paid attention, coordination with special assistants for children with special needs also not well established, so it is difficult to exchange information about the condition of children with special needs specifically. The purpose of this study was to determine the perceptions and attitudes of elementary school class teachers as facilitators of inclusive education for children with special needs at SDN Babakan 01 in the city of South Tangerang. The method used in this research qualitative research with a descriptive method aimed at understanding social phenomena from the perspective of the participants (people from whom the data is taken). Based on the results of the study, it can be concluded that the perceptions and attitudes of elementary school classroom teachers as facilitators of inclusive education for children with special needs at SD Negeri Babakan 01, South Tangerang city are still not by the system or regulations in carrying out inclusive programs, because there is still a lack of knowledge of classroom teachers about the characteristics of children with special needs can make it difficult for classroom teachers to deliver teaching materials, hinder the learning process in the classroom, and hinder the acceptance of teaching materials delivered by classroom teachers to children with special needs, making it difficult to optimize the potential that exists in children with special needs.